7
$\begingroup$

How Can I evaluate the following sum$$\sum_{m=0}^{\infty}\frac{2-\delta_m^0}{a}\frac{(-1)^m \lambda_0}{\lambda_0^2 -(\frac{m\pi}{a})}\cos\left(\frac{m\pi x}{a}\right)=\frac{\cos(\lambda_0 x)}{\sin(\lambda_0 a)}$$

I have read this in a research paper enter image description here I have tried evaluating the sum using finite cosine transform We have $$\frac{2}{a}\frac{1}{\lambda_0}+\frac{2}{a}\sum_{m=0}^{\infty}\frac{(-1)^m \lambda_0}{\lambda_0^2 -(\frac{m\pi}{a})}\cos\left(\frac{m\pi x}{a}\right)=f(x)$$ So $$\frac{(-1)^m \lambda_0}{\lambda_0^2 -(\frac{m\pi}{a})}=\int_{0}^{a} f(x)\cos\left(\frac{m\pi x}{a}\right) dx $$

How to find $f(x)$ ?

And Is there any other way to evaluate the sum ?

Thanks In advance.

$\endgroup$
  • $\begingroup$ $\displaystyle 1/\lambda_{0}$, $\displaystyle x$ and $\displaystyle a$ seem to have the same dimensions. So, something is wrong with the original statement. $\endgroup$ – Felix Marin May 18 '19 at 5:39
  • $\begingroup$ How is it that your LHS is $2a$ periodic but your RHS isn't? Otherwise, this would just be the Fourier series of your function in the interval $\left[-a,a\right]$. $\endgroup$ – eranreches May 18 '19 at 16:15
  • $\begingroup$ what do you meanby $\delta_m^0$? $\endgroup$ – G Cab May 19 '19 at 23:01
  • $\begingroup$ $\delta^0_m =1 $if m=0 and =0 otherwise $\endgroup$ – Mahmoud Hassan May 20 '19 at 18:36
  • $\begingroup$ Can you specify the domain of the constants $a$ and $\lambda_0$? Integer, real, or complex? Is $a>0$? I'm not sure your formula for $f(x)$ is correct. Note $\sum_{m=0}^\infty\frac{(2-\delta_{0,m})\,(-1)^m\,\lambda_0}{a \left(\lambda_0^2-\frac{m \pi}{a}\right)} \cos \left(\frac{m \pi x}{a}\right)=\frac{1}{a \lambda_0}+\frac{2 \lambda_0}{a}\sum_{m=1}^{\infty } \frac{(-1)^m }{\lambda_0^2-\frac{m \pi}{a}}\cos \left(\frac{m \pi x}{a}\right)$. $\endgroup$ – Steven Clark May 20 '19 at 22:20
2
+50
$\begingroup$

Focusing on the main task of the problem in the OP I shall calculate the sum starting at $m=1$ and dropping the overall factor $\lambda$, i.e. the expression

$$f(x) = \frac{2 }{a} \sum _{m=1}^{\infty } \frac{(-1)^m \cos \left(\frac{\pi m x}{a}\right)}{\lambda ^2-\frac{\pi m}{a}}\tag{1}$$

Assuming $\lambda ^2 \lt \frac{\pi}{a}$ we write

$$\frac{1}{\lambda ^2-\frac{\pi m}{a}} = - \int_{0}^{\infty} e^{-t (\frac{\pi m}{a}-\lambda ^2)}\, dt\tag{2}$$

and

$$\cos(\frac{m \pi x}{a}) = \Re \exp(i \frac{m \pi x}{a})$$

Substituting this into $(1)$ the /geometric) sum can be done under the integral:

$$\sum _{m=1}^{\infty } (-1)^m \exp \left(\frac{i \pi m x}{a}\right) \exp \left(-t \left(\frac{\pi m}{a}-\lambda ^2\right)\right)\\= -\frac{e^{t \left(-\left(\frac{\pi }{a}-\lambda ^2\right)\right)+\frac{\pi t}{a}+\frac{i \pi x}{a}}}{e^{\frac{\pi t}{a}}+e^{\frac{i \pi x}{a}}}$$

Integrating the negative this over $t$ according to $(2)$ and applying the missing factor gives

$$-\frac{2}{\pi} \left(-e^{\frac{i \pi x}{a}}\right)^{\frac{a \lambda ^2}{\pi }} B(-e^{\frac{i \pi x}{a}},1-\frac{a \lambda ^2}{\pi },0)\tag{3}$$

Here $B$ is the incomplete Beta function defined by

$$B(z,a,b) = \int_{0}^{z} t^{a-1} (1-t)^{b-1}$$

We now have to take the real part.

Selecting the simplified case $\lambda \to 0$ expression $(3)$ reduces to

$$\frac{2}{\pi} \log \left(1+e^{\frac{i \pi x}{a}}\right)$$

The real part and hence the sum is

$$f(\lambda\to 0)=\frac{1}{\pi} \log \left(4 \cos \left(\frac{\pi x}{2 a}\right)^2\right)\tag{4}$$

The case $0 \lt \lambda ^2 (\lt \frac{\pi}{a})$ can be extracted from $(3)$ as well. It will be left as an exercise in complex arithmetic to the reader.

For any $\lambda \ne \sqrt{\frac{\pi m}{a}}$ the sum can be expressed by the Hurwitz-Lerch transcendent as follows

$$f= \frac{1}{\pi} \left( e^{\frac{i \pi x}{a}} \Phi \left(-e^{\frac{i \pi x}{a}},1,1-\frac{a \lambda ^2}{\pi }\right) +e^{-\frac{i \pi x}{a}} \Phi \left(-e^{-\frac{i \pi x}{a}},1,1-\frac{a \lambda ^2}{\pi }\right) \right)\tag{5}$$

$\Phi $ is defined as

$$\Phi(z,s,a) = \sum_{k=0}^{\infty} z^k (k+a)^{-s} $$

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Thank you very much . $\endgroup$ – Mahmoud Hassan May 23 '19 at 11:08
  • $\begingroup$ I'll try to follow up the calculation for $(m \pi /a)^2$ to get $\frac{\cos(\lambda x)}{\sin(\lambda a)}$ $\endgroup$ – Mahmoud Hassan May 23 '19 at 11:32
  • $\begingroup$ @ Mahmoud Hassan Hint: after partial fraction decomposition you can use my results immediately. However, you won't get $\frac{\cos(\lambda x)}{\sin(\lambda x)}$. $\endgroup$ – Dr. Wolfgang Hintze May 24 '19 at 7:24
0
$\begingroup$

Too long for the comment.

The issue sum $$S_1 = \sum_{m=0}^{\infty}\frac{2-\delta_{m0}}{a}\frac{(-1)^m \lambda_0}{\lambda_0^2 -(\frac{m\pi}{a})}\cos\left(\frac{m\pi x}{a}\right),\tag1$$

where $\delta_{ij}$ is the Kronekker symbol,

can be considered as the particular case of $S_k$, where $$S_k = \frac{1}{a}\frac{1}{\lambda_0} + \frac{2}{a}\sum_{m=1}^{\infty}\frac{(-1)^m \lambda_0}{\lambda_0^2 -(\frac{m\pi}{a})^k}\cos\left(\frac{m\pi x}{a}\right).\tag2$$

Using known exponential Fourier series for cosine function

$$\cos(bz) = \dfrac{2b\sin(b\pi)}\pi\left(\dfrac1{2b^2}-\sum\limits_{m=1}^\infty \dfrac{(-1)^m\cos(mz)}{m^2-b^2}\right)\tag3$$

with the values $$b=\dfrac{\lambda_0a}\pi,\quad z = \dfrac{\pi x}a,$$

one can get $$\dfrac 1\pi\dfrac{\cos(\lambda_0x)}{\sin(\lambda_0a)} = \dfrac1{a\lambda_0} + \dfrac{2\lambda_0a}{\pi^2} \sum\limits_{m=1}^\infty \dfrac{(-1)^m\cos\left(\dfrac{m\pi x}{a}\right)}{\dfrac{\lambda_0^2a^2}{\pi^2}-m^2}=S_2.$$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.